Productive Waqf Governance for Ummah Economic Empowerment in Indonesia: A Literature Review and 5P Framework - Abdussalam; Santi Eka Panasiah; Sumadi Buton; Edy Setiawan (Journal of Contemporary Applied Islamic Philanthropy, 2026)
Purpose: This study analyzes productive waqf governance as an instrument for strengthening ummah economic empowerment in Indonesia and formulates the 5P Framework as a conceptual synthesis of recent literature. Methodology: The study applies a structured literature review with a descriptive-qualitative approach. Literature was traced through Google Scholar, Dimensions, GARUDA, DOAJ, and SINTA-indexed journal portals. The initial search produced 68 records. After duplicate removal, title-abstract screening, and full-text eligibility assessment, 10 scholarly articles and 3 official institutional or policy documents were retained as substantive sources. Three methodological sources were also used to support the review procedure, qualitative analysis, and literature-selection flow. Data were analyzed using qualitative content analysis through reduction, thematic classification, interpretation, model comparison, and synthesis. Findings: Productive waqf in Indonesia can be developed through asset-based waqf, cash waqf, partnership-based waqf, profit-sharing waqf, Cash Waqf Linked Sukuk, and digital waqf. The main barriers include limited nazhir professionalism, weak asset mapping, legal-administrative constraints, financing gaps, low waqf literacy, and insufficient transparency. The 5P Framework-Potential, Professionalization, Productivity, Partnership, and Public Trust-offers a governance-oriented contribution that connects waqf potential, institutional capability, productive utilization, accountable collaboration, and sustainable public confidence.